To determine which equation has the solution \( x = 3 \), we need to substitute \( x = 3 \) into each equation and see if the equation holds true.
-
Equation: \( 2x - 7 = -1 \) \[ 2(3) - 7 = -1 \ 6 - 7 = -1 \ -1 = -1 \quad (\text{True}) \]
-
Equation: \( 8x - 8 = 68 \) \[ 8(3) - 8 = 68 \ 24 - 8 = 68 \ 16 = 68 \quad (\text{False}) \]
-
Equation: \( 8x - 4 = 84 \) \[ 8(3) - 4 = 84 \ 24 - 4 = 84 \ 20 = 84 \quad (\text{False}) \]
-
Equation: \( 6x - 6 = -12 \) \[ 6(3) - 6 = -12 \ 18 - 6 = -12 \ 12 = -12 \quad (\text{False}) \]
From this, we see that the only equation that holds true when \( x = 3 \) is: \( 2x - 7 = -1 \).
Thus, the answer is: \( 2x - 7 = -1 \).